2021
DOI: 10.19127/bshealthscience.792782
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antimicrobial Activity of Various Plant Essential Oils on Vancomycin Resistant Enterococci (VRE) and Some Pathogenic Microorganisms

Abstract: In this study, it was aimed to determine the anti-bacterial activities of plant essential oils such as thyme, rosemary, sage, linden, black seed, bay leaf, peppermint, parsley, cinnamon and oleagen on vancomycin resistant enterococci (VRE) and pathogenic microorganisms of clinical importance. In the study, the inhibition zones of the plant extract of 10 plants prepared at 2.5 and 5 mg / ml concentrations of VRE and various pathogenic microorganisms were detected by Disk Diffusion and Agar Well Diffusion Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(17 reference statements)
0
0
1
Order By: Relevance
“…The favorable results in our study were found in the inhibition of vancomycin-resistant enterococci (VRE), which could pose a significant public health problem. Sage extracts have previously been described as good inhibitors of VRE even in the soft cheese matrix [48], as well as rosemary in vitro [49]. A more recent study by Duraisamy et al [50] showed an inhibitory effect of basil ethanol extracts against VRE, but this was not the case with our three strains.…”
Section: Antibacterial Capacity Of Plant Extractscontrasting
confidence: 53%
“…The favorable results in our study were found in the inhibition of vancomycin-resistant enterococci (VRE), which could pose a significant public health problem. Sage extracts have previously been described as good inhibitors of VRE even in the soft cheese matrix [48], as well as rosemary in vitro [49]. A more recent study by Duraisamy et al [50] showed an inhibitory effect of basil ethanol extracts against VRE, but this was not the case with our three strains.…”
Section: Antibacterial Capacity Of Plant Extractscontrasting
confidence: 53%